Propostas Pedagógicas para a Educação Física: a abordagem Crítico-Superadora e Crítico-Emancipatória 20 anos após suas sistematizações - Iora, Jacob Alfredo (2012)
The objective of this study is to analyze two theoretical points from the methodological Field of Physical Education (PE): the Critical Overcoming Approach (Colection of Authors, 1992), based on the historical and dialectical materialism and the Critical Emancipatory Approach (Kuns, 1994) formulated trough the phenomenological approach of human movement. This research is situated in the historical development of the pedagogical plan to PE, that is, the critics in relation to specificity - content, as well as, the realities that are shown beyond the classroom, the patio and the walls of the school, in fact, the society and its changes. Then yet, systematizing Critical Overcoming and Critical Emancipatory Approaches are dealt, in this study, as proposals that yet earned an important space in the epistemological field of PE. Sustained by Marxists foundations, it is possible emphasized that, in the last decades, this proposes have been the new center of different discussions and questions, mainly in relation to the development in the practical context. It is therefore important much progress to the knowledge area of PE, that goes on the deconstruction of the biological/technicist PE conception , as well as the formulation to the development of the critical pedagogic practice. In face of this changes in Chapter I and II, it was analyzed the existing theories in the education: critical, non critical; reproductively-critical and reflexive critical, its supports for the categories of content, pedagogical practice, work, knowledge theories, rationality of the mentioned proposes. In the chapter III, we aimed to check the critic to the proposal of PE, through the analyses of the real work in the pedagogical context of the extension projects at Santa Maria public schools. Then, twenty one years after the formulations, the Critical Emancipatory Approach become effective in the teaching situations investigated among the view of the extensions projects, as well as, in the reality of public school. The pedagogical practice developed in the investigated context shows that the deconstruction of the typical characteristics of sports of high efficiency and the reconstruction of Sport connected with teaching its specificities for all that is one PE with educational aims. The Critical Overcoming Approach represented in the final point as one theory of PE has been supported as critic. By having as a central pillar the work, it is possible, to understand this as an educative principle, criticizing the fundamental properties of capitalism, as for example the private ownership of means of production and the society division of classes. By protecting socialism, its affectivity has been real, because, it in its theory of knowledge and rationality is the overcome the limits for its affectivity, that is the passage from capitalism to socialism